2016
DOI: 10.1186/s13007-016-0102-1
|View full text |Cite
|
Sign up to set email alerts
|

Automated video tracking of thrips behavior to assess host-plant resistance in multiple parallel two-choice setups

Abstract: BackgroundPiercing-sucking insects cause severe damage in crops. Breeding for host-plant resistance can significantly reduce the yield losses caused by these insects, but host-plant resistance is a complex trait that is difficult to phenotype quickly and reliably. Current phenotyping methods mainly focus on labor-intensive and time-consuming end-point measurements of plant fitness. Characterizing insect behavior as a proxy for host-plant resistance could be a promising time-saving alternative to end-point meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(85 citation statements)
references
References 27 publications
1
84
0
Order By: Relevance
“…Screening large numbers of plants for identification of resistance sources is vital for resistance breeding programmes . Recently, a high‐throughput phenotyping method has been described that uses automated video tracking of WFT behaviour . However, a reproducible high‐throughput method assessing thrips damage is still lacking.…”
Section: Future Directions Of Wft Control: ‘Omics’ Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening large numbers of plants for identification of resistance sources is vital for resistance breeding programmes . Recently, a high‐throughput phenotyping method has been described that uses automated video tracking of WFT behaviour . However, a reproducible high‐throughput method assessing thrips damage is still lacking.…”
Section: Future Directions Of Wft Control: ‘Omics’ Technologiesmentioning
confidence: 99%
“…118 Recently, a high-throughput phenotyping method has been described that uses automated video tracking of WFT behaviour. 119 However, a reproducible high-throughput method assessing thrips damage is still lacking. Similarly, HTS systems testing for active metabolites against WFT deriving from plants or microbials are absent.…”
Section: High-throughput Screeningmentioning
confidence: 99%
“…The dual-choice assay with pure chrysanthemol glycoside was carried out using automated video tracking system as described (Thoen et al, 2016). We dissolved the chrysanthemol glycoside in 25% sugar water at the same concentration (434 lg/mL, 1.08 mM) which in transgenic chrysanthemum and further prepared a series of dilutions (217, 108.5, 54.25, 0 lg/mL).…”
Section: Aphid Dual-choice Assay With Leaf Nonvolatile Contents and Pmentioning
confidence: 99%
“…Although leaf disc screening methods are widely accepted and used for pest resistance screening (van Rijn, Mollema, & Steenhuis-Broers, 1995;Thoen et al, 2016) and Maharijaya et al (2011) convincingly showed the correlation between the detached leaf assay, leaf discs and whole plant damage, the question remains whether screening approaches using leaf discs reliably predicts resistance at the whole plant level for our set of Capsicum accessions.…”
Section: Introductionmentioning
confidence: 96%